SISTEM INFORMASI RIWAYAT PERJALANAN (SIRP) MASYARAKAT DIMASA PANDEMI BERBASIS WEBSITE (Studi Kasus: Kecamatan Sungai Geringging) - darmansah darmansah; Tomy Tomy Nanda Putra; Willi Novrian Willi Novrian (Universitas Alma Ata, 2021)
The Corona virus or covid-19 began to appear in wuhan china at the end of 2019. Until now the corona virus has been a disease that has spread tremendously in countries in the world, none of which is Indonesia. To prepare accurate and reliable information in order to suppress the spread of the corona virus in Indonesia, an information system is needed. The Sungai Geringging District Government is a government in Padang Pariaman Regency which is currently collecting data on the travel history of its people during the pandemic manually or has not maximized computerization and technology. This of course makes the sub-district government in recording data, managing community data entering and leaving the government environment ineffective and inefficient. To assist the Sungai Geringging District Government in collecting data and disseminating information, it is necessary to build a website-based SIRP (Travel History Information System) information system. In designing this SIRP (Travel History Information System) the researcher used UML (Unified Modeling Language) modeling. In this study, UML was used to facilitate researchers when designing the system to be made. The method that researchers apply in this study is the prototyping method. With the construction of the Travel History Information System (SIRP) during the pandemic, it is hoped that the Sungai Geringging District Government can easily manage community data that enters and exits the government environment. In addition, the public can easily find out information on how many people are under surveillance (ODP) and people without symptoms (OTG) and other information related to the corona virus.